Alice 3 in action with Java - Adams, Joel 1957- (Cengage Learning, 2015)
Provides a meaningful, motivating introduction to object-oriented programming with 3D animation, riveting examples and a spiral approach that uses Alice before circling back to apply the same skills to success in Java